2018
DOI: 10.3389/fmicb.2018.00837
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole-Urea in a Buccal Film as a New Trend for Treatment of Resistant Mouth Fungal White Patches

Abstract: A growing concern about Candida albicans is the emergence of high incidence of resistance against antifungal agents, which requires searching for new medications or improving the response to the existing members. The objective of this work was to evaluate the effectiveness of the miconazole in the absence and presence of urea, as a penetration enhancer, against C. albicans. In addition to, formulating both of them in a polymer film to be used topically for treatment of mouth fungal white patches caused by C. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The local film solubility curve model represented the absorption of solution from the moist infected area, which was considered the first step in the treatment resulting in dryness of the infected area, to some extent, and release of the active substances to penetrate the deeper skin layers exerting a localized effect. The chemical interaction between the drug and the film component could be expected as reported by Mady et al (2018). They proved the disappearance of all characteristic drug peaks under those of the film components following application of IR scan.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The local film solubility curve model represented the absorption of solution from the moist infected area, which was considered the first step in the treatment resulting in dryness of the infected area, to some extent, and release of the active substances to penetrate the deeper skin layers exerting a localized effect. The chemical interaction between the drug and the film component could be expected as reported by Mady et al (2018). They proved the disappearance of all characteristic drug peaks under those of the film components following application of IR scan.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, increasing the concentration of urea to 20 or 40% in combination with miconazole reduced only MIC dramatically to 0.001, while it did not affect the MFC (0.004 mg/L). Mady et al (2018) investigated the effect of miconazole/urea combination against resistant C. albicans and proved its effectivity in reducing MIC from 32 to 0.0625 µg/mL, resulting in a synergistic effect. Hultenby et al (2014) reported that 50% topical K101 nail solution composed of urea, propylene glycol, and lactic acid was effective against T. rubrum cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different approaches have identified effective combinations of natural compounds with marketed drugs (Prasad and Kapoor, 2005; Spitzer et al, 2017). Mady et al (2018) demonstrated synergistic activity between Miconazole and urea for treating C. albicans . Other examples include the use of novel compounds such as APX001A and APX2020 in combination with FCZ with a FICI of 0.37 (Shaw et al, 2018), calcium channel blockers such as amlodipine, nifedipine, bendipine, and flunarizine with FCZ with FICI <0.5 (Liu et al, 2016), licofelone and FCZ (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 97%